PENGARUH PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN BIBIT DUA VARIETAS DURIAN (Durio zibethinus M.) HASIL SAMBUNG SAMPING (SIDE GRAFTING). - Irang Enjau; Susylowati Susylowati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The objective of this experiment was to know the effect of the interaction between Nasa liquid organic fertilizer concentration and  varieties durian, to know optimum Nasa liquid organic fertiliezer concentration to the growth could on Salisun varieties and Monthong varieties, and to know to the growth varieties the best of effect Nasa liquid organic fertilizer. The experiment was conducted at the village Bayur, District Sempaja North, Samarinda City, East Kalimantan Province.  Experiment factorial 2x4 was arranged in a Randomized Completely Block Design (RCBD) and eight times replication.  The first factor is the durian plant varieties (V) consisting of two, namely, v1= Salisun varieties and v2= Monthong varieties, and the second factor is the Nasa liquid organic fertilizer concentration (N) consinting of four levels, namely, n0= 0 mL L-1 water (control), n1= 2 mL L-1 water, n2= 4 mL L-1 water, n3= 6 mL L-1 water.  Data analyzed by Analysis of Variance, and continued by the  Least Significant Difference (LSD) test of 5%  to compare the average of two treatment. The results showed that treatment of  varieties  durian plant (V) significant different on the average increasing number of leaf at age 60 days after trans planting, and average increasing number of leaf age 90 and 120 days after trans planting,  but did not significant on the average increasing to the plant height, number of branch plant, and increasing plant stem diameter.  The treatment of  Nasa liquid organic fertilizer concentration (N), and interaction  between of varieties and Nasa liquid organic fertilizer concentration (VxN) did not significant on the all of variables observed.